Analysis of frequency ranges of heart rate variability and estimation errors of respiratory sinus arrhythmia in aging - V. M. Bahilin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The clinical significance of heart rate variability (HRV) was assessed at the end of the last century, despite the fact that HRV studies have been conducted since the mid-19th century. In recent years, HRV has been increasingly used for non-invasive monitoring of the autonomic nervous system. However, the interpretation of HRV features is still not fully understood and widely discussed. It is known that HRV fluctuations are created by various regulatory systems of the body, which have different natural frequencies. The estimated HRV parameters are SDNN and RMSSD indicators – standard deviations of a number of RR-intervals and a number of first differences of RR-intervals, respectively. The purpose of the article was to calculate the power decrease with aging in different frequency ranges, analyze the errors of spectral estimates, and compare the spectral estimates of RSA with the values of RMSSD indicators. Simultaneous ECG and respiration records from the Fantasia Physio Bank database were used as initial data. For reference estimates, the powers in the range of respiration rate found from the records of respiration measurements are taken. It is shown that with age the power of the HF range decreases most rapidly, and the VLF range decreases most slowly. HF oscillation amplitudes are compared with RMSSD values. It is proposed to consider the RMSSD indicator as an assessment of the speed parameter of the regulatory system. Spectral methods are used to estimate the power of individual frequency ranges. For non-invasive monitoring of the autonomic nervous system, spectral estimates of the power of the LF and HF ranges are used. With aging, stress, and various diseases, the activity of regulatory systems decreases, but it remains unclear in which regulatory systems and to what extent violations occur.